Detection of common pathogens and their association with husbandry factors in pre-weaned piglets with diarrhoea - Fong, Michelle Wai Cheng; Abd Rahaman, Nor Yasmin; Ooi, Peck Toung; Tee, C. Y.; Lai, J. Y. Q.; Thong, J. J. K. (Malaysian Veterinary Medical Association, 2024)
Pre-weaned piglet diarrhoea significantly impacts the swine industry. This study investigates common pathogens associated with this condition, including Clostridium perfringens, Coronaviridae, Cystoisospora suis, and Salmonella spp., and examines their correlation with husbandry factors. A total of 183 rectal samples from diarrhoeic piglets across 15 farms in Malaysia were analysed, revealing Clostridium perfringens (97.96%) and Coronaviridae (77.05%) as the predominant pathogens. Notably, 73.77% of samples exhibited co-infection by two to three pathogens, with significant correlations identified between co-infection rates and farrowing crate emptying time. Specifically, crate emptying time of 3-5 days was associated with a significantly lower percentage of co-infections (p<0.05) compared to 1 day and 7 days emptying time, providing actionable insights for farmers to enhance management strategies and control measures against these pathogens.